Underworld : from Hoboken to Hollywood - Kaz, 1959- (Fantagraphics Books, 2016)
"In addition to his career as an Emmy winning writer for animation (Cartoon Network's Camp Lazlo, Disney's Phineas and Ferb, and Nickelodeon's SpongeBob Squarepants), Kaz has been unleashing his id and corrupting generations with his Harvey nominated weekly Underworld comic strip since 1992. Underworld hilariously depicts sordid doings in a surreal city, stuffed with almost-parodies of famous comic strip characters, a healthy dose of cigarette smoking cats, cute little saccharin-cuddly creatures, media-damaged kids and much more."--Publisher's description.